Sediment Organic Phosphorus Fractionation and Spatial Variation in Langat River, Malaysia (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
Langat River in Malaysia is an important river with active development on its basin. Excess nutrients such as organic phosphorus introduced through these developments can change the trophic level of the river and by using simple and cost-effective methods, preliminary information on the status of organic phosphorus can aid in the understanding of the complex biogeochemical cycling of phosphorus in rivers. Water and sediment samples were collected from 10 points along the river. The proportion of organic phosphorus was quantified based on the fractions through sequential fractionation. The results indicate that the downstream section of the river has a high percentage of organic phosphorus (48.22%) compared to the upstream and midstream combined. The major fraction in all sites was the non-labile fraction comprising of 60–78% of the total organic phosphorus extracted. Humic acid derived from organic matter either autochthonous or allochthonous sorb organic phosphorus into the sediments and stays internal loading in the river. Moderately labile fulvic acid-bound organic phosphorus has lesser contribution in the sediments but may play an important role in increasing the dissolved phosphorus levels in the waters. Labile forms also contribute lesser in the sediments except when the river is closest to the sea due to higher sedimentation rate facilitated by tidal action. Organic phosphorus in the sediments of Langat River currently may not pose an immediate threat but presents a future risk to the ecosystem considering the river status in accumulating organic phosphorus.
Keywords: Biogeochemical; Dissolved phosphorus; Humic substances; Internal loading; Labile fraction